Socio-Economic Instance of Ethnic Group in Bangladesh: A Case Study of Dhaka City - Beg, Tahrima Haque; Khan, Sunjida; Afrina, Taskin; Hossain, Md Shakib; Zayed, Nurul Mohammad (International Journal of Accounting & Finance Review, 2020)
In Bangladesh, an ethnic community such as barber, cobbler, washerman, porter become victims of severe discrimination despite the constitutional declaration that protects citizen's equal rights regardless of their race, caste, religion. This study focuses on various minor and untouchable groups in our society. Due to various reasons like lack of education, extreme poverty, lack of proper healthy atmosphere, etc. they could not organize themselves to establish their rights. Consequently, they remain in the darkness of the community. They also remain out of development efforts, untouchable and downtrodden. A cross-sectional survey was carried out from 12th February to 27th February 2020 in different areas in the capital city. The purpose of the study is to determine the lifestyle, family background, education level, and socioeconomic impact to access credit among these groups of people.